Pemanfaatan Limbah Organik Rumah Tangga Untuk Pembuatan Pupuk Kompos di Desa Alue Sungai Pinang Kecamatan Jeumpa Kabupaten Aceh Barat Daya - Arif Sardi; Khairatul Ulya (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to raise public awareness of the importance of utilizing household waste to make compost in Alue Sungai Pinang Village, Sub-District Jeumpa, Southwest Aceh Regency. By making compost, the household waste can be used as fertilizer and help create a clean environment from waste (zero waste). The method used in this research consists of 3 stages, namely: observation, preparation and implementation of activities. Compost is produced using materials originating from the household waste of Alue Sungai Pinang Village residents in the form of vegetable remains, rotting fruits, sawdust, and manure. Household waste that previously had no economic value can be processed or reused to become compost. This compost fertilizer can be applied to residents' plantations or to grow plants around the house such as vegetables, fruits and decorative plants.